2014
DOI: 10.1111/imb.12133
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase‐like gene family in the brown planthopper, Nilaparvata lugens

Abstract: Chitinases are important enzymes required for chitin degradation and reconstruction in insects. Based on a bioinformatics investigation, we identified 12 genes encoding putative chitinase-like proteins, including 10 chitinases (Cht), one imaginal disc growth factor (IDGF) and one endo-β-N-acetylglucosaminidase (ENGase) in the genome of the brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae). These 12 genes were clustered into nine different groups, with 11 in glycoside hydrolase family 18 groups (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
181
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(196 citation statements)
references
References 30 publications
14
181
1
Order By: Relevance
“…OfChtIII contains 987 amino-acid residues and is composed of four domains: a predicted TM domain (residues 7-29), two catalytic domains, GH18A (residues 94-461) and GH18B (residues 530-889), and a CBM14 domain (residues 922-976). Its physiological role remains elusive (Zhu et al, 2008;Pesch et al, 2016;Xi et al, 2015;Su et al, 2016). In situ immunological staining as well as gene-expression pattern analysis suggested that the role of OfChtIII is linked to the chitin-synthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…OfChtIII contains 987 amino-acid residues and is composed of four domains: a predicted TM domain (residues 7-29), two catalytic domains, GH18A (residues 94-461) and GH18B (residues 530-889), and a CBM14 domain (residues 922-976). Its physiological role remains elusive (Zhu et al, 2008;Pesch et al, 2016;Xi et al, 2015;Su et al, 2016). In situ immunological staining as well as gene-expression pattern analysis suggested that the role of OfChtIII is linked to the chitin-synthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Chitinases, a multi-gene family, have widely different functions, which are associated with cuticle turnover, nutrition digestion, and disease resistance (Arakane and Muthukrishnan, 2010;Merzendorfer, 2013). With the completion of genome sequencing of some insects, numerous chitinases and chitinase-like proteins have been identified in many insects, including Drosophila melanogaster (Zhu et al, 2004), Tribolium castaneum (Zhu et al, 2008a), Acyrthosiphon pisum (Nakabachi et al, 2010), Anopheles gambiae (Zhang et al, 2011), Bombyx mori (Pan et al, 2012), and Nilaparvata lugens (Xi et al, 2014). These studies revealed the distinct functions of chitinase family genes in insects and provided a biological rationale for the presence of numerous chitinase-like proteins (Zhu et al, 2008b;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation showed that, from 2000 to 2010–2011, rice pests caused a loss of up to 48 million ha in China (Zhao et al 2014). The hemimetabolous Brown planthopper Nilaparvata lugens Stål (Hemiptera: Delphacidae), which causes huge yield losses directly, is one of the most destructive insect pests, as they can only feed and breed on rice or wild rice (Xi et al 2014, 2015a,b). This pest damages rice plants by directly sucking the phloem sap and transmits plant viruses (Ghaffar et al 2011, Yang et al 2014).…”
mentioning
confidence: 99%
“…Originally, insecticide control was an important and very convenient way to control and decrease pest populations, but its improper use has led to pest resurgence and resistance, and to the accumulation of chemical residues (Xi et al 2014). In N. lugens , gene-function studies have also shown that RNAi of target genes could be used a pest-control strategy (Wang et al 2012, 2015; Xi et al 2014, 2015a,b; Liu et al 2015; Zhao et al 2016; Yang et al 2017). …”
mentioning
confidence: 99%